## Trending News

Promoted

Anonymous

# -1 = 1 ???

-1 = (-1) ^ 3 = (-1) ^ 6/2 = [(-1) ^ 6] ^ 1/2 = 1^ 1/2 = 1 !!!

how's that? Where the truc?

### 6 Answers

Relevance

- 1 decade agoFavorite Answer
1 has two square roots... -1 and 1. That's how it works. Every positive number has negative and positive roots. (-1)*(-1) = 1 and (1)*(1) = 1.

- How do you think about the answers? You can sign in to vote the answer.
- Anonymous1 decade ago
(-1)^3 = (-1) ^ 6/2 is false

that rule is only when the number inside the parentheses is positive

Source(s): http://en.wikipedia.org/wiki/Invalid_proof

Still have questions? Get your answers by asking now.